Publication Growth, Authorship Collaboration, and Citation Patterns: A Comparative Bibliometric Study of Selected Indian LIS Journals (2010-2024) - Mondal, Debdas (Journal of Data Science, Informetrics, and Citation Studies, 2026)
Bibliometric analysis provides a systematic, quantitative approach to evaluating research productivity, authorship patterns, and citation impact in scholarly communication. While single-journal studies have traditionally dominated LIS research assessment in India, comparative analyses involving multiple journals offer a more comprehensive understanding of research trends and scholarly influence. This study presents a comparative bibliometric analysis of five leading Indian Library and Information Science (LIS) journals: IASLIC Bulletin, Annals of Library and Information Studies (ALIS), DESIDOC Journal of Library and Information Technology, SRELS Journal of Information Management over the period 2010-2024. Data were collected from Scopus, Web of Science, and Google Scholar using the Publish or Perish software and analysed using standard bibliometric indicators, including annual publication growth, authorship patterns, degree of collaboration, total and average citations, h-index, and author productivity. The findings reveal a steady increase in research output, a predominance of collaborative authorship, and notable variation in citation impact among journals. The study highlights the evolving nature of LIS research in India, the growing importance of collaborative practices, and inter-journal differences in scholarly visibility and impact. These insights are valuable for researchers, editors, and policymakers seeking to enhance research quality, collaboration, and influence within the LIS domain.
Keywords: Authorship Collaboration; Bibliometric Analysis; Citation Patterns; Indian LIS Journals; Library and Information Science